Ownership Structure and Initial Public Offerings - Aggarwal, Reena (World Bank, Washington, DC, 2014)
The authors study the relationship between ownership structure, corporate governance, and the initial public offering (IPO) process. They examine equity ownership by different institutions, such as foreign and domestic financial institutions, banks with and without lending relationships, venture capitalists, and corporations prior to an IPO. The authors also analyze the relationship between ownership structure and corporate governance. They use a unique dataset of 152 Indian IPOs during the period 1999-2001 to analyze ownership of shares by main groups of shareholders. The authors find a relationship between ownership structure and firm-specific factors such as sales, leverage, and profitability, and IPO characteristics such as percentage of equity locked up, gross proceeds, and exchange of listing. There is also a strong relationship between ownership by different types of institutions. Ownership is also tied to bank lending relationships. Finally, the authors find strong relationships between ownership types and corporate governance. For example, firms with foreign investors are more likely to have an outside chief executive officer and offer an employee stock option plan.